Dynamics of core-excited ammonia: disentangling fragmentation pathways by complementary spectroscopic methods. Issue 2 (16th November 2022) - Travnikova, Oksana; Hosseini, Farzad; Marchenko, Tatiana; Guillemin, Renaud; Ismail, Iyas; Moussaoui, Roba; Journel, Loïc; Milosavljević, Aleksandar R.; Bozek, John D.; Kukk, Edwin; Püttner, Ralph; Piancastelli, Maria Novella; et al.
Abstract : Combining resonant Auger spectroscopy and electron–ion coincidence measurements, the complex relaxation patterns of core-excited ammonia are revealed. Decay processes leading to the same fragment but with different timescales are enlightened. Abstract : Fragmentation dynamics of core-excited isolated ammonia molecules is studied by two different and complementary experimental methods, high-resolution resonant Auger spectroscopy and electron energy-selected Auger electron–photoion coincidence spectroscopy (AEPICO). The combined use of these two techniques allows obtaining information on different dissociation patterns, in particular fragmentation before relaxation, often called ultrafast dissociation (UFD), and fragmentation after relaxation. The resonant Auger spectra contain the spectral signature of both molecular and fragment final states, and therefore can provide information on all events occurring during the core-hole lifetime, in particular fragmentation before relaxation. Coincidence measurements allow correlating Auger electrons with ionic fragments from the same molecule, and relating the ionic fragments to specific Auger final electronic states, and yield additional information on which final states are dissociative, and which ionic fragments can be produced in timescales either corresponding to the core-hole lifetime or longer. Furthermore, we show that by the combined use of two complementary experimental techniques we are able to identify more electronic states of the NH2 + fragment with respect to the single one already reported in the literature.